PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KETERLIBATAN KERJA YANG DIMEDIASI OLEH BUDAYA ORGANISASI PADA PEGAWAI NEGERI SIPIL DINAS KESEHATAN KOTA BAU-BAU - S Syarifa Fauzin; Ibnu Hajar; Nofal Nur; Yusuf Montundu; La Ode Asfahyadin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This research was conducted with the aim of looking at the direct effect of transformational leadership on job involvement, the direct effect of compensation on job involvement. And see the mediating role of organizational culture in influencing the relationship between transformational leadership on job involvement and the influence between compensation on job involvement. This study used 74 respondents as civil servants of the Bau-Bau City Health Office. The sampling technique in this study was carried out by means of the census technique so that the entire population was used as the research sample. The research data were collected using a questionnaire and analyzed using PLS. The results of this study indicate that there is a positive and significant influence between transformational leadership on job involvement, transformational leadership also has a positive and significant effect on organizational culture. Meanwhile, compensation has a positive effect on job involvement although it does not affect it significantly. The same results were also found on the effect of compensation on organizational culture that compensation affects organizational culture positively, although not significantly. Meanwhile, mediation was found to influence the relationship between transformational leadership and job involvement partially. Meanwhile, the mediation of organizational culture on the effect of compensation on job involvement is full mediation.